ASSESSMENT MEDIA FOR OFFLINE AND ONLINE WRITING TESTS AT JUNIOR HIGH SCHOOLS DURING THE COVID-19 PANDEMIC - Siti Zulfa; Nida Husna; Dhila Nurul Azmi; Didin Nuruddin Hidayat (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2023)
ABSTRACTThis study explores writing assessment media used by English teachers in offline and online assessment procedures during the last Covid-19 pandemic. This qualitative study incorporates a case study design with five English teachers of junior high schools serving as research participants selected purposively. The data for this study were gathered using semi-structured interviews with English teachers and students writing documents. The study results indicate that English teachers utilized different media in their offline and online assessments. For the offline activities, they used conventional paper-based media to collect writing samples, administer written tests, and conduct writing projects to measure students' attainment levels of their writing skills. For the online activities, they used platforms familiar to them, including Google Classroom, Google Form, and WhatsApp, and most of them assessed their students using multiple choice questions; yet some of the teachers did paper-based tests but submitted them to the online media. The teachers used rubrics for both assessment modes and provided feedback accordingly. One important implication of this research for post-pandemic English teaching underscores the significance of teachers' initiatives of alternating offline and online media to assess students' writing skills and maximize students' learning experiences in response to actual classroom constraints and opportunities.ABSTRAKPenelitian ini bertujuan untuk mengeksplorasi berbagai bentuk media penilaian menulis yang digunakan oleh guru bahasa Inggris dalam kegiatan offline dan online selama Covid-19. Penelitian ini menggunakan studi kualitatif dengan desain studi kasus. Partisipan penelitian ini meliputi lima guru bahasa Inggris di sekolah menengah pertama yang dipilih dengan teknik purposive sampling. Instrumen penelitian menggunakan wawancara semi-terstruktur untuk setiap guru bahasa Inggris dan dokumen tulisan siswa. Hasil penelitian menunjukkan bahwa guru bahasa Inggris menggunakan dan menerapkan media penilaian menulis yang berbeda dalam kegiatan luring dan daring selama dan pasca pandemi Covid-19. Selama kegiatan offline, guru bahasa Inggris menggunakan kertas sebagai media produk tulisan, tes tertulis, dan proyek untuk menilai tulisan siswa. Sementara itu, selama kegiatan daring, guru bahasa Inggris menggunakan media platform daring seperti Google Classroom, Google Form, dan WhatsApp; guru menilai dengan menggunakan pertanyaan pilihan ganda namun beberapa guru masih menggunakan kertas untuk dikirimkan ke media tersebut. Guru bahasa Inggris menggunakan rubrik khusus dan memberikan umpan balik dalam menilai tulisan siswa selama kegiatan offline dan online. Pengalaman baru dalam mengintegrasikan media penilaian alternatif dalam menulis dapat bermanfaat bagi guru bahasa Inggris dan siswa, terutama untuk membantu tugas menulis.